2018
DOI: 10.1002/cche.10103
|View full text |Cite
|
Sign up to set email alerts
|

Blending studies using wheat and lentil cotyledon flour—Effects on rheology and bread quality

Abstract: Background and objectives: Lentil (Lens Culinaris. Medik) is a highly nutritious food staple widely consumed within India subcontinent and the Mediterranean region. Although gaining popularity in western diets, wheat will continue to be a major crop as it can be used to manufacture a wide range of products. The nutritional benefits of lentils are acknowledged, particularly as a source of high protein so the incorporation of lentil flour into wheat-based foods has the potential to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 27 publications
4
33
2
2
Order By: Relevance
“…Regarding the quality of the resultant breads, Mohammed et al (2014) reported that the replacement of wheat flour with chickpea flour at 10%-30% lowered the loaf volume, caused darker color of the crust, and resulted in a harder texture of the bread. Similar baking results have been demonstrated for flours composited with various pulse flours at different levels in other studies (Ficco et al, 2018;Portman et al, 2018).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding the quality of the resultant breads, Mohammed et al (2014) reported that the replacement of wheat flour with chickpea flour at 10%-30% lowered the loaf volume, caused darker color of the crust, and resulted in a harder texture of the bread. Similar baking results have been demonstrated for flours composited with various pulse flours at different levels in other studies (Ficco et al, 2018;Portman et al, 2018).…”
Section: Introductionsupporting
confidence: 89%
“…( Table 4 and Figure S2), and the value fits well within the range of CWRS hard wheat flour (63.1%-68.4%; Bourré et al, 2019;Portman et al, 2018). The incorporation of raw and germinated yellow pea flours progressively reduced the water absorption of the flour blends, whereas the use of raw and germinated faba bean flours did not follow the same trend.…”
Section: Farinographsupporting
confidence: 70%
See 1 more Smart Citation
“…Hence, inclusion of field peas in the production of traditional cereal‐based products (e.g. bread, pasta, and biscuits) will increase the protein content of the products …”
Section: Resultsmentioning
confidence: 99%
“…There is an increasing interest in utilizing pulses in wheat‐based products with blends . The demand for gluten‐free baked products has led to exploration of the nutritional properties of baked good from pulses like chickpea and lupins .…”
Section: Introductionmentioning
confidence: 99%